People’s Perspective for Milky Stork: A Case from South Sumatra, Indonesia - Iqbal, Muhammad; Ridwan, Ahmad (Journal of Wetlands Ecology, 2008)
DOI: 10.3126/jowe.v1i1.1571No abstract.   Journal of Wetlands Ecology Vol.1(1/2) 2008, p.7